The gender gap in pension saving - Jonathan Cribb; Heidi Karjalainen; Laurence O'Brien (Institute for Fiscal Studies (IFS), 2023)
In this report, we document differences in pension incomes and pension saving between men and women in the UK, and analyse the drivers behind these differences. In particular, we examine two different 'gender pension gaps'. First is the gap in average private and state pension incomes between men and women who are already over state pension age. Second is the gap in average pension saving between working-age men and women, with a focus on how this is affected by differences in labour market experiences, and how the gaps differ for private sector employees, public sector employees and the self-employed.
Keywords: 330; Savings; pensions and wealth; Ageing; Gender; Inequality; Private pensions; Retirement; Savings; State pensions